2016
DOI: 10.1098/rsob.160064
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 signalling and autophagy are involved in diabetes mellitus-induced defects in the development of mouse placenta

Abstract: It is widely accepted that diabetes mellitus impairs placental development, but the mechanism by which the disease operates to impair development remains controversial. In this study, we demonstrated that pregestational diabetes mellitus (PGDM)-induced defects in placental development in mice are mainly characterized by the changes of morphological structure of placenta. The alteration of differentiation-related gene expressions in trophoblast cells rather than cell proliferation/apoptosis is responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…The mature mouse placenta is a layered structure that is composed of the maternal decidua, the junctional zone, and the labyrinth zone. The junctional zone separates the labyrinth from the maternal decidua, whereas the labyrinth zone provides the interface for exchange between maternal and fetal circulations [29,30]. In the present study, we found that dietary proline supplementation enhanced the area of the labyrinth zone in the placenta, therefore constituting a greater surface for nutrient and oxygen exchange, as well as the removal of embryonic wastes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The mature mouse placenta is a layered structure that is composed of the maternal decidua, the junctional zone, and the labyrinth zone. The junctional zone separates the labyrinth from the maternal decidua, whereas the labyrinth zone provides the interface for exchange between maternal and fetal circulations [29,30]. In the present study, we found that dietary proline supplementation enhanced the area of the labyrinth zone in the placenta, therefore constituting a greater surface for nutrient and oxygen exchange, as well as the removal of embryonic wastes.…”
Section: Discussionsupporting
confidence: 58%
“…Serial sections were stained with hematoxylin and eosin (H&E) and photographed using a fluorescence microscope (Olympus IX50) linked to the NIS-ELEMENTS F3.2 software. The areas of decidua, labyrinth, and junctional zone were determined as previously described [29]. A minimum of six fields for each placental section, 12 placentas per group, were randomly selected for the morphometric qualification of placentae.…”
Section: Placental Morphological Analysismentioning
confidence: 99%
“…In our previous study, we found that autophagy is involved in diabetes mellitus-induced defects in the development of mouse placenta. [51] Studies have shown that NF-κB is not only a pro-inflammatory factor, but also regulates the process of autophagy. IKK-NF-κB axis is a context-dependent regulator of autophagy [52] ROS may also promote autophagy, and the imbalance of cell autophagy might also contribute to the observed placental phenotypes directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…IKK-NF-κB axis is a context-dependent regulator of autophagy [52] ROS may also promote autophagy, and the imbalance of cell autophagy might also contribute to the observed placental phenotypes directly or indirectly. [ 51 53 54 ] So there may be a closed loop in the GDM placenta, high glucose stimulates TLR4s pathway, and there is an imbalance between the internal and external environment of placental villus trophoblast cells. In order to suppress this imbalance, autophagy is up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…High-glucose concentrations also hindered the invasiveness of the HTR-8/SVneo trophoblast cells derived from the chorionic villi explants of human first-trimester placenta [39]. Another study demonstrated that upregulation of invasion-related genes, and also of invasive trophoblast marker genes, following high glucose treatment of the human BeWo choriocarcinoma cell line [40], suggesting there is a cell line-dependent difference in the response to hyperglycemic conditions. Unlike these previous studies, in which cells were continuously exposed to various glucose conditions during differentiation, here we focused on the effect of different extracellular glucose levels on stem cells of the trophoblast lineage using mouse TSCs.…”
Section: Discussionmentioning
confidence: 99%